Learning Nahwu Using Mind Mapping Method in a Modern Islamic Boarding School - Kojin Kojin; Choiruddin Choiruddin (STAI Hubbulwathan Duri, 2022)
At the beginning of the twentieth century, many muslim intellectuals studied in various well-known universities in Europe. They returned to their home countries to bring concepts of modern educational methods like the mind mapping method to facilitate the learning of Islamic sciences, especially Arabic. This present research aims at discussing planning, steps, and evaluation adopted in learning Nahwu using the mind mapping method at a Modern Islamic Boarding School. In this research, the authors adopted a case study as the research design with the type of field study. The techniques of data collection applied were in-depth interviews, participant observations, and documentation study, while the data were analyzed through data reduction, data display and data verification. The results showed that the preparation of the lesson plan for Nahwu with the mind mapping method started from determining basic competences, continued with the learning indicators, the materials, the method used, and the instrument of evaluation that would be used. The steps of the learning activities were as follows: introduction, presenting the core materials, evaluation, and closure. Evaluation in learning Nahwu in this method was made by examining the products, performances, and tests administrated to the students either in their daily, mid-term and final tests.